2014
DOI: 10.1111/1744-9987.12230
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Dilution Hemodiafiltration With a Heparin‐Grafted Polyacrylonitrile Membrane

Abstract: The aim of this multicenter, prospective study was to explore the possibility of carrying out routine sessions of post-dilution hemodiafiltration with a polyacrylonitrile membrane grafted with heparin (HeprAN) and reduced anticoagulation. Forty-four patients from eight centers were included in the study and treated by means of post-dilution on-line hemodiafiltration with automatic control of TMP, according to three different modalities tested consecutively: phase 1, polyethersulfone filter primed with heparini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
(29 reference statements)
0
5
0
1
Order By: Relevance
“…In THDFS, the unfractionated heparin dose was ∼10% higher in the HDF group when compared with HD patients [ 14 ]. A recent study, using heparin-coated membranes in ol-HDF, showed that the dose of LMWH could be reduced safely without an increased risk of clotting [ 36 ].…”
Section: Optimization Of Convection Volume In Clinical Practicementioning
confidence: 99%
“…In THDFS, the unfractionated heparin dose was ∼10% higher in the HDF group when compared with HD patients [ 14 ]. A recent study, using heparin-coated membranes in ol-HDF, showed that the dose of LMWH could be reduced safely without an increased risk of clotting [ 36 ].…”
Section: Optimization Of Convection Volume In Clinical Practicementioning
confidence: 99%
“…De las tres membranas utilizadas en nuestro estudio, la PH fue la que menos heparina precisó, tan sólo 33 mg, misma situación que reflejan otras investigaciones [19][20][21] MCM: Membrana de corte medio de poliariletersulfona y polivinilpirrolidona, HBPM: heparina de bajo peso molecular; FAVn: fístula arteriovenosa nativa; CVCt: catéter venoso central tunelizado. †Test chi cuadrado o test exacto de Fisher para frecuencias inferiores a 5, en la comparación por tipo de dializador frente al resto de variables.…”
Section: Originalesunclassified
“…Compared to cellulose membranes, organic synthetic membranes possess more physical‐chemical advantages in terms of pore size, hydraulic permeability and filtration capacity . Polysulfone (PS) and polyethersulfone (PES) membranes are two of the most classical synthetic membranes, which have been widely used in clinical hemodialysis due to their excellent filtering properties and biocompatibility, thermal stability, mechanical strength, and chemical inertness.…”
Section: Microfluidic Hemodialysis Systems and Componentsmentioning
confidence: 99%